(untitled) (Innovate Conferences, 2025)
A correct daily lifestyle is the basis of physical, mental health and success in life for every person. During this period, it is especially important for students to establish a correct daily routine. An incorrect daily routine can have a serious negative impact on the health of students. Decreased academic performance: With improper daily routine and poor planning of study time, students face difficulties in the learning process. Postponing homework and exam preparation until the last minute will lead to lack of time, which will lead to stress and poor grades.